Essays in money and interest - Robertson, Dennis Holme (London : Collins, 1966)
The book is a compilations of essays from Robertson on Money and interest rates. He examined the issues of the behavioural pattern of interest rate as well as the theories of money in the stability of the economy.
Bibliographical footnotes.
usc 29/6/17
Loans
Keywords: Money; Interest